An introduction to experimental phasing of macromolecules illustrated by SHELX; new autotracing features. Issue 2 (4th February 2018) - Usón, Isabel; Sheldrick, George M.
Abstract : Experimental phasing of macromolecular crystals is described and explained, with the emphasis on its implementation in the programs SHELXC, SHELXD and SHELXE, which are also used in a number of macromolecular structure‐solution pipelines. Abstract : For the purpose of this article, experimental phasing is understood to mean the determination of macromolecular structures by exploiting small intensity differences of Friedel opposites and possibly of reflections measured at different wavelengths or for heavy‐atom derivatives, without the use of specific structural models. The SHELX programs provide a robust and efficient route for routine structure solution by the SAD, MAD and related methods, but involve a number of simplifying assumptions that may limit their applicability in borderline cases. The substructure atoms ( i.e. those with significant anomalous scattering) are first located by direct methods, and the experimental data are then used to estimate phase shifts that are added to the substructure phases to obtain starting phases for the native reflections. These are then improved by density modification and, if the resolution of the data and the type of structure permit, polyalanine tracing. A number of extensions to the tracing algorithm are discussed; these are designed to improve its performance at low resolution. Given native data to 2.5 Å resolution or better, a correlation coefficient greater than 25% between the structure factors calculated from such a trace and the native data is usually a good indication that the structure has been solved.